The Portrait of Isaac in Genesis 27: Between Synchronic and Diachronic Readings of Patriarch’s Character - Rozonoer, Anna (Verbum Vitae, 2022)
Modern critical reception characterizes patriarch Isaac as a particular character type: the schlemiel. This article provides a tour through the cumulative evidence for this comedic read, focusing on Genesis 27, the blessing of Jacob. It provides a revised narratological and literary context, arguing that Isaac’s fivefold questioning demonstrates not confusion, but awareness: he knows exactly which son is in front of him. The paper presents an alternative narratological and literary context for Isaac, framing his questions in terms of the editing process: a synchronic reading of Isaac’s acumen is corroborated by evidence from diachronic reading. The redaction history of the Isaac material in chapter 26 yields a number of points suggesting the dependence of the Abraham material on the Isaac narrative. A number of features indicate a stronger, less subordinate Isaac figure based on the earlier tradition revealed by a complex transmission history than the image arising from the mainstream synchronic reading of chapter 27 seems to depict.